RANCANG BANGUN PENGELOLAAN BANDWIDTH INTERNET MENGGUNAKAN METODE QUEUE TREE DENGAN ROUTER MIKROTIK DI PT XYZ - Salim, Agus; Wijaya, Tanto; Pusparini, Nur Nawaningtyas (ISTEK WIDURI, 2023)
Basically, the use of internet activities in companies is very dense, causing various problems, among the problems encountered related to internet connection is bandwidth usage that has not been optimally regulated, so that no matter how much bandwidth capacity is available, it will not meet the needs of internet bandwidth usage if it is not managed properly. . In order for internet user bandwidth allocation to be distributed evenly, bandwidth management is needed to overcome the existing bandwidth limitations. Bandwidth management aims to find a solution so that all user computer devices get internet bandwidth allocation and can find out how to manage good bandwidth so that user devices get a fair or even distribution of bandwidth. The methodology for implementing bandwidth management with the queue tree method is to observe a running network system, identify problems, collect data, then design a configuration system. After going through the design process then carrying out the configuration stage, and if the configuration is successfully applied then proceed to the testing phase using several user computers assisted by using the wireshark application to find out incoming or received data packets, the next stage is monitoring using monitoring applications such as Torch Winbox, speedtest or wireshark and the final stage is evaluation or management such as configuration backups and so on. This research and testing also takes into account Quality of Services (QoS) parameters such as throughput, delay, jitter, and packet loss to find out in more detail the calculation of packet traffic that has been captured by the wireshark application. So that with good design, proper configuration, careful monitoring, an even, optimal bandwidth usage and quality internet connection is produced, so that the implementation of the queue tree method of bandwidth management provides an effective solution in managing bandwidth allocation.